1993
DOI: 10.1364/josab.10.001006
|View full text |Cite
|
Sign up to set email alerts
|

Transient grating diffraction from an interface between two materials: theory and experimental application

Abstract: A general theory for transient grating diffraction from both sides of a single interface is developed. The grating is assumed to have an arbitrary amplitude on both sides of a bound interface with the grating wave vector parallel to the interface. The specific spatial origin of the diffracted light is described for both the reflected and the transmitted geometries of diffraction. In the reflected geometry the signal is dominated by diffraction from a region near the interface that is a small fraction of an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…29,30,32,33 On the other hand, such an acoustic wave also causes modulation of the refractive index. 27,28 Nelson and co-workers 33 showed that the oscillations of TRG signals at the surface are mainly caused by the surface displacement modulation and not by the refractive index modulation in the case of the surface measurement. In addition to the report, we found from diffraction theory considerations that the refractive index modulation was a minor component of the signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,32,33 On the other hand, such an acoustic wave also causes modulation of the refractive index. 27,28 Nelson and co-workers 33 showed that the oscillations of TRG signals at the surface are mainly caused by the surface displacement modulation and not by the refractive index modulation in the case of the surface measurement. In addition to the report, we found from diffraction theory considerations that the refractive index modulation was a minor component of the signal.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33] Two temporally coincident laser pulses ͑pump pulses͒ with the same wavelength produce optical interference fringes on and under the sample surface. These optical fringes cause spatial modulations of the refractive index and surface displacement.…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The interface selectivity was achieved by the probe reflection at the interface. 21,30,31 Under this experimental configuration, analysis of the dynamics should be much simpler compared with the case of the short penetration depth, because the transport of the thermal energy or molecules along the vertical direction to the grating vector is minor. Most of the TG dynamics is determined by the transport along the grating vector.…”
Section: A Forced Light Scatteringmentioning
confidence: 99%
“…Even if there is no interface displacement, any periodic spatial modulation of optical properties in the phase that reflects the probe light diffracts the reflected probe light to a direction that satisfies the phase matching condition. The theoretical treatment of the probe reflected TG signal was presented by Fishman et al 31 The effective probe depth (d eff ) is given by…”
Section: A Forced Light Scatteringmentioning
confidence: 99%